The Influence Of Good Corporate Governance On Environmental, Social, And Governance (ESG) Disclosure (Case In Consumer Non-Cyclicals Sector Companies Listed On The Idx, 2017-2021) - Farida Titik Kristanti; Erris Rayhan Fahrezi (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
The objective of the study is to measure the influence of board size, women on the board, independent commissioner, and audit committee on Environmental, Social, and Governance (ESG) Disclosure on the company sector consumer non-cyclical listed on the Indonesia Stock Exchange (IDX) in 2017-2021. Method research used in this study is a quantitative approach. The study's Disclosure of Environmental, Social, and Governance (ESG) data originates from the Company's Sustainable Report for five years, from _ 2017-2021. The method taking samples used in this study is purposive sampling, obtained by eight companies’ samples for five years of research (2017-2021) with 40 units analysis—data analysis using analysis multiple linear regression. Based on the results, the study can conclude that women on the board influence Environmental, Social, and Governance (ESG) Disclosure. In contrast, the board size, independent commissioner, and audit committee are ineffective toward Environmental, Social, and Governance (ESG) Disclosure. Kindly simultaneous variable independent, namely board size, women on the board, independent commissioner, and influential audit committee, to variable dependent on Environmental, Social, and Governance (ESG) Disclosure.